2021
DOI: 10.3389/fnana.2021.664695
|View full text |Cite|
|
Sign up to set email alerts
|

Convergent and Divergent Mechanisms of Epileptogenesis in mTORopathies

Abstract: Hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) due to mutations in genes along the PI3K-mTOR pathway and the GATOR1 complex causes a spectrum of neurodevelopmental disorders (termed mTORopathies) associated with malformation of cortical development and intractable epilepsy. Despite these gene variants’ converging impact on mTORC1 activity, emerging findings suggest that these variants contribute to epilepsy through both mTORC1-dependent and -independent mechanisms. Here, we review th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 134 publications
1
31
0
Order By: Relevance
“…Hyperactivation of mTORC1 signaling during neurodevelopment impairs cortical neuron migration and morphogenesis, resulting in neuronal misplacement across the cortical layer and cytomegaly. These FMCD hallmarks are consistently recapitulated in all current FMCD mouse models with mTORC1 hyperactivity (Nguyen and Bordey, 2021). Induction of c4E-BP1 CA expression at P28 in Rheb CA mice was sufficient to reduce neuronal cytomegaly, but not misplacement.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Hyperactivation of mTORC1 signaling during neurodevelopment impairs cortical neuron migration and morphogenesis, resulting in neuronal misplacement across the cortical layer and cytomegaly. These FMCD hallmarks are consistently recapitulated in all current FMCD mouse models with mTORC1 hyperactivity (Nguyen and Bordey, 2021). Induction of c4E-BP1 CA expression at P28 in Rheb CA mice was sufficient to reduce neuronal cytomegaly, but not misplacement.…”
Section: Discussionmentioning
confidence: 79%
“…FMCDs in TSC, FCDII, and HME share core histopathological features characterized by cortical mislamination, neuronal heterotopia, and the presence of dysmorphic cytomegalic neurons with enhanced mTORC1 activation (Lim and Crino, 2013). Numerous studies in mouse models of FMCD have shown that treatment with the mTORC1 inhibitor, rapamycin, prevents FMCD formation and reduces seizures (Ostendorf and Wong, 2015; Nguyen and Bordey, 2021). These findings emphasize the central role of mTORC1 dysregulation in the etiology of these disorders and identifying the downstream mechanisms of mTORC1 that lead to FMCD and epilepsy is an active area of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR pathway has been implicated as a mechanism by which diverse genetic mutations and acquired abnormalities lead to a final common pathway of seizures ( Griffith and Wong, 2018 ). The 4E-BP2 is the major neuronal mTORC1-downstream and is a translational repressor, which inhibits cap-dependent translation ( Nguyen and Bordey, 2021 ). The ablation of 4E-BP2 in PV+ interneurons, but not in other subtypes, is sufficient to promote reduced latency and increased severity to PTZ-induced seizures.…”
Section: Parvalbumin Role In Epilepsy: Historical Investigation Of Te...mentioning
confidence: 99%
“…Macrocephaly is frequently described in CPS associated with brain tumor, for example in Gorlin syndrome, related to a constitutional PV of a gene of the Sonic Hedgehog (SHh) pathway (PTCH1 or SUFU) [4], in Cowden syndrome related to PTEN germline PV [5] or more recently in DICER1-syndrome [6]. Brain malformations may be reported before or at the occurrence of the brain tumor: abnormal cortical development in the tuberous sclerosis complex (TSC) of Bourneville [7], agenesis of the corpus callosum or vascular developmental anomalies in patients with Constitutional MisMatch Repair Deficiency (CMMRD) [8], focal area of high signal intensity (FASI) on T2/FLAIR images in NF1 patients [9]. Specific skin lesions are also often part of the clinical phenotype characterizing these patients and are referred as neurocutaneous syndromes.…”
Section: Key Pointsmentioning
confidence: 99%